Chronic subdural hematoma following ventriculoperitoneal shunt: A case report - Karki, Mohan; Roka, Yam Bahadur; Pandit, Mukesh; Yadav, Sachidanand (Birat Journal of Health Sciences, 2020)
Chronic Subdural Hematoma (CSDH) is rare complication following ventriculoperitoneal (VP) shunt for hydrocephalus. A fourteen year/male presented with complain of gradually weakness of right sided limbs, severe headache, seizure and slurring of speech after two and half month of VP shunt placement for congenital hydrocephalus. CT scan head was done and it reported left CSDH with mass effect. Patient was managed with left parietal single burr-hole and CSDH evacuation.